Ökonomisierungsprozesse und die Soziologie ökonomischen Denkens als Grundlagen der (sozio-)ökonomischen Bildung - Lenger, Alexander [Verfasser] (My University, 2018)
"Ziel (sozio-)ökonomischer Bildung ist es, Lernende zur Selbstbestimmung und zu gesellschaftlicher Verantwortung in wirtschaftlichen, politischen und sozialen Zusammenhängen zu befähigen. Hierzu aber müssen zwei zentrale gegenwärtige Phänomene an Lehramtsstudierende der sozial- und wirtschaftswissenschaftlichen Verbundfächer vermittelt werden. Erstens die zunehmende Ökonomisierung und Vermarktlichung sämtlicher Lebensbereiche. Und zweitens die Rolle, die die Wirtschaftswissenschaften bei der Etablierung und Veränderung dieser neuen Organisations- und Lebensformen einnehmen. Im vorliegenden Beitrag werde ich zeigen, dass die Ökonomisierung sämtlicher Lebensbereiche ihren Ursprung insbesondere in der performativen Wirkung der Wirtschaftswissenschaften bei der Etablierung und Veränderung neuer Organisationsformen und subjektiver Handlungsmuster hat. Diese Prozesse wiederum prägen im Sozialisationsprozess das ökonomische Denken von Schüler*innen und müssen entsprechend an den Ausgangspunkt der berufs-und wirtschaftspädagogischen Ausbildung gestellt werden." (Autorenreferat; BIBB-Doku)

"The aim of (socio-)economic education is to enable students to be self-determined and to assume social responsibility in economic, political and social matters. For this purpose, however, two key current phenomena must be conveyed to student teachers of social and economic science subjects. The first one is the increasing economisation and marketisation of all aspects of life. The second one is the role played by economic sciences in establishing and changing these new forms of organisation and ways of life. In this paper, I will show that the economisation of all aspects of life has its origin primarily in the performative effect of economic sciences on the establishment and change of new forms of organisation and subjective behaviour patterns. These processes, in turn, shape a student's economic thinking during their socialisation process and must therefore be placed at the start of teacher training in vocational and economic education. The paper is structured as follows: First, I will present key findings on a sociology of economic thinking. I will focus in particular on the formative influence of economic sciences. I will then demonstrate why the phenomenon of economisation must be a key aspect of (socio-)economic education. In order to advance this argument, I will briefly outline different ways to interpret economisation and, as an example, discuss the economisation of universities as organisations. I will demonstrate, in particular, that the phenomenon of economisation occurs at the societal, organisational and individual level at the same time. The paper will conclude that it is essential for pedagogical research and training in the field of vocational and economic education to focus on these two aspects." (author's abstract; BIBB-Doku)
Economisation Processes and the Sociology of Economic Thinking as a Basis for (Socio-)Economic Education
Keywords: T 4.6 Wirtschafts- und Rechtswissenschaften; Ökonomische Bildung; Lehrerausbildung; Wirtschaftswissenschaft; Ökonomisierung; Sozioökonomie